ANALISIS PEMBUKTIAN UNSUR-UNSUR PASAL 114 ayat (2) UNDANGUNDANG No 35 TAHUN 2009 TENTANG NARKOTIKA (Studi Terhadap Putusan Pengadilan No.: 246/Pid.Sus/2016/PN. Skt.) - HANDAYANI, DYAH NUNING (Dinamika Hukum, 2017)
This study aims to analyze Proof Elements of Article 114 of Law 35 of2009 on Narcotics in Decision No. : 246 / Pid.Sus / 2016 / PN. Skt.Background research that the drug problem has become a nationalproblem that is increasingly troubling. One case was handled and narcotics casesalready decided by the District Court of Surakarta namely Decision No. 246 /Pid.Sus / 2016 / PN. Skt. The verdict is an example of the application of Article114 paragraph (2) of Law 35 of 2009 on Narcotics. In this study will be assessedon the evidentiary elements contained in the article in consideration of the judge.The research method with the approach of legislation and case approach.Data consisted of secondary data in the form of primary legal materials, secondaryand tertiary. In addition to the primary data in the form of observations.Normative data were analyzed qualitatively.The results showed that the legal provisions and principles of evidence inproving the criminal case has been applied. This is evident in the consideration ofjudges consisting of consideration of the facts also legal considerations.Consideration of the facts pertaining to testimony of witnesses, testimony of thedefendant, confirmed the testimony of witnesses and information from thedefendant, the evidence and documentary evidence. Eventually all of the evidenceand the evidence supports the fulfillment of the elements of the offenses chargedthat the defendant was sentenced.Keywords: Proof, Act 35 of 2009 on Narcotics, the Court Decision No .: 246/Pid.Sus / 2016 / PN. Skt